The influence of high-intensity interval running bouts on distal anterior femoral cartilage in competitive distance and middle-distance runners - Evans, R. J.; Battersby, H. S.; Williams, L. E.; Pamukoff, D. N. (Journal of Sports Sciences, 2025)
Competitive runners compared with recreational runners have increased odds of osteoarthritis and running-related injury, potentially from different running types. We compared distal anterior femoral cartilage deformation in competitive runners following a continuous and high-intensity interval run (10 × 400 m, 300 m jog) and evaluated the association between running kinetics and cartilage deformation. Twenty-four competitive runners (11 females and 13 males), between 18 and 35 years old underwent femoral cartilage ultrasound imaging before and after both running conditions in a counterbalanced order 2-7 days apart. Footwear was instrumented with force-sensing insoles to extract peak ground reaction force, loading rate, and impulse. A 2 (time) by 2 (condition) ANOVA with repeated measures evaluated the change in cartilage thickness after running between conditions. The lateral cartilage region showed greater deformation after interval compared with continuous running (p = 0.003). A main effect of time was seen where cartilage was thinner after running compared with baseline regardless of condition (1.92 (1.82, 2.02) vs. 1.83 (1.73, 1.93) mm; mean difference = -0.094 (-0.147, -0.042) mm, p = 0.001). No significant associations were found between cartilage deformation and loading rate, peak ground reaction force, or impulse (all r < 0.32, all p > 0.05). Interval running contributed to greater lateral distal anterior femoral cartilage deformation.